The Effect of Capital Structure, Leverage, and Profitability on LQ45 Company Value Period 2020-2022 (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Objectives: Company value is an investor's prediction of how big the chance of success of a  company is. The value of the company can be seen from the high and low stock prices. This study  aims to determine the effect of capital structure, leverage, and profitability on firm value in LQ45  companies for the 2020-2022 period. Methodology: This study uses a quantitative approach using secondary data. The analysis  technique used in this study is multiple linear regression. The data test used is the normality test,  heteroscedasticity autocorrelation, and hypothesis testing. Finding: The results of the study show that partially capital structure has an effect on firm value  with a significance value of 0.0000.05 and profitability has an effect on firm value with a significance value of  0.000